An assessment of alternative postharvest technologies for the disinfestation of fresh Cape Flora cut flowers for export from South Africa - Huysamer, Anton Jean (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.